Targeting Fatty Acid Synthase Modulates Metabolic Pathways and Inhibits Cholangiocarcinoma Cell Progression - Tomacha, Jittima; Dokduang, Hasaya; Padthaisong, Sureerat; Namwat, Nisana; Klanrit, Poramate; Phetcharaburanin, Jutarop; Wangwiwatsin, Arporn; Khampitak, Tueanjit; Koonmee, Supinda; Titapun, Attapol; Jarearnrat, Apiwat; Khuntikeo, Narong; et al. (Frontiers in Pharmacology, 2021)
An aberrant regulation of lipid metabolism is involved in the pathogenesis and progression of cancer. Upregulation of lipid biosynthesis enzymes, including acetyl-CoA carboxylase (ACC), fatty acid synthase (FASN) and HMG-CoA reductase (HMGCR), has been reported in many cancers. Therefore, the elucidation of lipid metabolism changes in cancer is essential for the development of novel therapeutic targets for various human cancers. The current study aimed to identify the abnormal expression of lipid-metabolizing enzymes in cholangiocarcinoma (CCA) and to evaluate whether they can be used as the targets for CCA treatment. Our study demonstrated that a high expression of FASN was significantly correlated with advanced stage disease in CCA patients. In addition, survival analysis showed that a high expression of FASN and HMGCR were correlated with a shorter survival of CCA patients. Furthermore, FASN knockdown inhibited the growth, migration and invasion in KKU055 and KKU213 cells. In addition, FASN knockdown induced cell cycle arrest and apoptosis of CCA cells. Moreover, a metabolomics study revealed that adenosine diphosphate (ADP) showed strong candidate metabolite significantly different between the control and FASN knockdown groups. Purine metabolism is the most relevant pathway involved in FASN knockdown in KKU213 cells. These findings provide new insights into the mechanism associated with FASN knockdown in CCA cells. Therefore, targeting FASN may serve as the novel CCA therapeutic strategy.